THE CYTOKINES IL-1B AND TNF-A AND THE METABOLIC PROFILE IN COWS WITH HYPERKETONEMIA: A LITERATURE REVIEW - de Souza, Marcelo Ribeiro; de Oliveira, Luís Eduardo Rangel Batinga; Soares, Pierre Castro; de Souza , Paulo Roberto Eleutério (Seven Editora, 2024)
Hyperketonemia is the most prevalent metabolic disease in the transition period of productive cows. It is characterized by the increase of ketone bodies in body tissues and fluids, in addition to changes in metabolic profiles and cytokine expression, which can result in significant economic losses and damage to animal health. Objective: To conduct a literature review addressing the main aspects related to hyperketonemia, with emphasis on changes in the metabolic profile and expression of the cytokines IL-1β and TNF-α during the transition period. Methodology: The review was based on articles found in the databases, published between 1972 and 2024, using specific terms such as "hyperketonemia", "transition period" and "metabolic profile". Literature review: Hyperketonemia develops in response to negative energy balance, when energy demand exceeds dietary intake, leading to mobilization of body reserves and increased non-esterified fatty acids (NEFAs) in the blood. These fatty acids are metabolized in the liver, favoring ketogenesis and resulting in metabolic disorders. The metabolic profile is an essential tool to assess the metabolic health of the herd, allowing the identification of changes in biochemical parameters, such as glucose, NEFAs, proteins and hormones. This monitoring reveals the relationship between metabolism and inflammatory responses, and is crucial for the early detection of disorders. The cytokines IL-1β and TNF-α, released during inflammatory processes, play an essential role in the transition period of dairy cows, contributing to the amplification of the inflammatory response associated with hyperketonemia. Conclusion: Early detection through biomarkers, such as β-hydroxybutyrate and NEFAs, is essential to prevent hyperketonemia. Inflammatory alterations, such as the elevation of IL-1β and TNF-α, reinforce the importance of integrated strategies for nutritional, genetic and immunological management, aiming to minimize damage to animal health and reduce economic losses. DOI: https://doi.org/10.56238/sevened2024.037-100